The Theories of the Sleep Regulation in the Human Organism - Vincze, Janos; Vincze-Tiszay, Gabriella (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Sleeping is accompanied by a physiological narrowing of consciousness, during which the central nervous system and the whole body can relax and regenerate. Ever since human consciousness was formed during the process of becoming a human being, but also from infancy to the early stages of the development of consciousness, humans have known the fact of sleeping and its necessity for the body to rest and “be reborn”. A seventy-year-old human spends approx. twenty years, or one-third of their life, asleep. During sleep, their connection with the outside world is more or less lost, but in the meantime they experience exciting dreams that are difficult for rational thinking to grasp. Are different theories of the sleep: Pavlov’s conception, Hess Conception, instinctive action, biological clock.